1976
DOI: 10.1073/pnas.73.5.1631
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-stimulated amino acid uptake into isolated membrane vesicles from Balb/c 3T3 cells transformed by simian virus 40.

Abstract: Mediated uptake of amino acids by membrane vesicles isolated from Balb/c 3T3 cells transformed by simian virus 40 has been demonstrated. Initial rates of transport of radioactively labeled L-leucine and a-aminoisobutyric acid were enhanced by the addition of NaCl (100 mM) to the reaction mixture at the start of the uptake process. This enhancement included a prominent "overshoot" during initial uptake. Slight stimulation of a-aminoisobutyric acid uptake was seen with K+, but none with Li+. The mediated nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This implies that the energy of a Na+-electrochemical gradient is used to drive AIB uptake. These findings are in agreement with those of Quinlan et al (18). Both reports describe the Na+-dependent amino acid uptake into membrane vesicles derived from tissue-culture cells.…”
Section: Membrane Fractionationsupporting
confidence: 83%
“…This implies that the energy of a Na+-electrochemical gradient is used to drive AIB uptake. These findings are in agreement with those of Quinlan et al (18). Both reports describe the Na+-dependent amino acid uptake into membrane vesicles derived from tissue-culture cells.…”
Section: Membrane Fractionationsupporting
confidence: 83%
“…Changes in pH, intracellular and extracellular calcium, osmolarity, and temperature appear to modulate NF-B activation by DNA-damaging agents. Interestingly, some of these changes can be observed with neoplastic transformation, within tumor microenvironments in various cancer types, and during radiation therapy and chemotherapy (8,33,43,64,71,92). Therefore, understanding the mechanisms responsible for enhancement (e.g., low pH, higher temperature) and the decrease (e.g., high osmolarity) of NF-B activation may provide novel strategies to prevent NF-B activation and to increase the efficacy of anticancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have reported that Na+ stimulates the uptake of amino acids, such as L-leucine, a-aminoisobutyric acid (AIB), and L-alanine, in membrane vesicles from virally transformed and nontransformed mouse fibroblasts (2)(3)(4)(5)(6)(7)(8)(9). Studies in this laboratory have demonstrated that mediated uptake of L-leucine and AIB by membrane vesicles from mouse fibroblasts transformed by simian virus 40 is stimulated by a NaCl gradient (external > internal) (2,5). In those studies it was shown that this enhancement is Na+ specific and includes a prominent "overshoot," namely, a transient intravesicular accumulation above the equilibrium level (i.e., active transport) during the initial uptake phase.…”
mentioning
confidence: 99%